The Impact of Fundamental and Technical Factors on Bank Stock Prices in Indonesia - Muhammad Yahya; Abdul Haris (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the influence of fundamental and technical factors on the stock prices of banking companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The study addresses the need for investors and company management to understand better the determinants of stock value in the banking sector. Research Method: This research employs a quantitative approach using secondary data. The population consists of 47 banking companies listed on the Indonesia Stock Exchange during the observation period. Data were analyzed using classical assumption tests, multiple linear regression, the coefficient of determination, the correlation coefficient, and hypothesis testing using simultaneous and partial tests. Results and Discussion: The findings show that the current ratio, return on assets, and debt-to-asset ratio have a positive and significant effect on banking stock prices. Total asset turnover has a negative but insignificant effect. From the technical factor perspective, interest rates have a positive and significant effect on stock prices, while inflation has a negative and significant effect. These results indicate that both internal financial performance and external macroeconomic conditions influence banking stock valuation. Implications: The findings provide practical guidance for investors in making investment decisions and for banking management in improving financial performance. Originality: This study integrates fundamental financial ratios and macroeconomic technical indicators to explain banking stock price movements in Indonesia.